Investigating on critical pedagogy in EFL classrooms: consciousness, practice and perceived problems (Journal of Tikapur Multiple Campus, 2018)
Although critical pedagogy has brought about positive changes in the field of education by shifting from traditional pedagogy to emancipatory pedagogy, not much attention has been paid to the implementations and problem side aspect in Nepal. This paper investigated the consciousness of English language teachers in the tenets of critical pedagogy. Moreover, it also presented the discussion of how Nepali teachers teaching English as a foreign language (EFL) at higher education institutions practice the critical pedagogy approach and delved the problems the teachers face when put the theory into action. I employed the mixed methods design where both quantitative and qualitative data were collected. I explored the informed consciousness of teachers about the critical pedagogy. Though they have not been following the exactly the same critical pedagogy procedure of practice in the EFL, they have been trying to be the active agent of transformation by applying the techniques like dialogue, debate, reflective practices, allowing the learners experiences, opinions in the classroom discussions. However, the teachers’ and students, status quo tendency and adopting the safe method are found as the major difficulties of proper practice of critical pedagogy in EFL classroom.